Induction of Pseudoactinorhizae by the Plant Pathogen Agrobacterium rhizogenes - Berg, R. Howard (1992)
Infection of Elaeagnus angustifolia cotyledonary wounds by Agrobacterium rhizogenes strain NCPPB 2659 resulted in the formation of pseudoactinorhizae on roots differentiated from callus. These pseudoactinorhizal root nodules were anatomically indistinguishable from the actinorhizae induced by the plant's microsymbiont Frankia. This unusual hairy root phenotype provides support for the concept that the genetic program for actinorhiza morphogenesis resides in the plant's genome.